2021
DOI: 10.1002/cctc.202001889
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Electrochemical Water Oxidation Activity of Au Supported Cobalt Oxide upon Addition of Cr: Insights using in situ Raman Spectroscopy

Abstract: Mixed metal oxides based on cobalt oxide are important target material as water oxidation catalyst in alkaline media. Significant enhancement of electrochemical oxygen evolution activity was observed for Au supported cobalt oxide, upon addition of Cr. CoO x /Au and Co[Cr]O x /Au were studied side by side to understand the effects of the addition of Cr in such a system. The presence of Cr resulted in a significant lowering of onset potentials~150 mV. In-situ Raman spectroscopy was used to characterize the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The peak at 503 cm −1 under higher potentials suggests the dominant presence of CoOOH due to the reason that only part of the Co 3+ species can be oxidized to Co 4+ . Overall, the spectroscopic results clearly evidence that Co 4+ species starts to form at 1.2 V and this agree well with recent study where CoO x deposited on Au is studied by Raman spectroscopy [16] . With similar spectra features, the authors concluded that the onset potential for the formation of CoO 2 containing Co 4+ is as low as 1.14 V. Based on the observed potential‐dependent activity towards oxidation of HMFCA and FFCA, it is therefore proposed that the anodic current towards HMF oxidation at 1.1 V is due to the indirect oxidation between Co 3+ and formyl group, where Co 3+ as generated electrochemically acts as the chemical oxidants [6, 17] .…”
Section: Resultssupporting
confidence: 92%
“…The peak at 503 cm −1 under higher potentials suggests the dominant presence of CoOOH due to the reason that only part of the Co 3+ species can be oxidized to Co 4+ . Overall, the spectroscopic results clearly evidence that Co 4+ species starts to form at 1.2 V and this agree well with recent study where CoO x deposited on Au is studied by Raman spectroscopy [16] . With similar spectra features, the authors concluded that the onset potential for the formation of CoO 2 containing Co 4+ is as low as 1.14 V. Based on the observed potential‐dependent activity towards oxidation of HMFCA and FFCA, it is therefore proposed that the anodic current towards HMF oxidation at 1.1 V is due to the indirect oxidation between Co 3+ and formyl group, where Co 3+ as generated electrochemically acts as the chemical oxidants [6, 17] .…”
Section: Resultssupporting
confidence: 92%
“…Overall, the spectroscopic results clearly evidence that Co 4+ species starts to form at 1.2 Vand this agree well with recent study where CoO x deposited on Au is studied by Raman spectroscopy. [16] With similar spectra features,t he authors concluded that the onset potential for the formation of CoO 2 containing Co 4+ is as low as 1.14 V. Based on the observed potential-dependent activity towards oxidation of HMFCA and FFCA, it is therefore proposed that the anodic current…”
Section: Resultsmentioning
confidence: 88%
“…The introduction of the Cr 3+ component in the CoCr LDH would have resulted in the stabilisation of the CoOOH species without conversion to the Co 4+ species. Stabilisation of lower oxidation states of Co (Co 2+ and Co 3+ ) warrant better hydroxyl coverage than the higher oxidation state of Co 4+ , [85] thereby leading to an early onset of OER.…”
Section: Chromium Electrocatalysts For Oer In Alkaline Mediummentioning
confidence: 99%
“…From their observations, they conclude that doping IrO 2 with Cr, Ru or Pb is beneficial for OER because of the weakening of free energy formation of O* compared to that on pure IrO 2 . Another study involving a noble metal investigated the effect of Cr on the CoO x /Au catalytic system using isotope labelled in‐situ Raman spectroscopy and XPS analysis [85] . The electrocatalysts (Co a Cr b O x /Au) were prepared by immersing Au foils in the respective varying metal ion (Co 2+ and Cr 3+ ) solutions and were compared to CrO x /Au, the pure Au foil substrate, and CoO x /Au.…”
Section: Chromium Electrocatalysts For Oer In Alkaline Mediummentioning
confidence: 99%